If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4y = -1 Solving x + 4y = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. x + 4y + -4y = -1 + -4y Combine like terms: 4y + -4y = 0 x + 0 = -1 + -4y x = -1 + -4y Simplifying x = -1 + -4y
| 3x-0.5=1.05 | | 1/2+3/5= | | 7(x-3)=5x+29 | | 5n+4=n+36 | | 8=100b+7 | | 48w^2+6=0 | | 11-9x=57-23 | | 7(v-4)=3(3+v)-1 | | 8+5m=908 | | n/7+3/7= | | 2-1y-4y=7 | | 18=3x+2y | | 18=3y+2x | | 18=2x+3y | | 20=4c+10 | | 3x+6(0.5)=42 | | 7=5u-73 | | -2.3(x-8)=3.7(x+4) | | 4x^2+20x-3=0 | | 6p-7=17 | | 5x-4=25x-6 | | 12x+7=7x+27 | | 4(X^2-1)=4x^2 | | (3w+8)(9-w)=0 | | (3z+6)(4z+9)= | | 2xw*3w= | | 5(5pq+5r)+5pq= | | (9-w)(3w+8)=0 | | 3-7n=-4n+12 | | 15=16x-3 | | -5x+125=0 | | -5a+3=2a+10 |